Sumablay sa pagsablay a study on the lived experiences of UP Visayas Tacloban College extended students. - Ador, Helena May A.; Alegre, April Hannah E.; Tonolete, Karla Joy N. (Helena May A. Ador, April Hannah E. Alegre, and Karla Joy N. Tonolete, 2019)
The study explored the lived experiences and psychological well-being of delayed to graduate students of the University of the Philippines Visayas Tacloban College. The research has sought to answer the questions: (1) What experiences of UP undergraduate students leads to their delay to degree? (2) How does not being able to graduate on time affect their psychological well-being? and (3) What strategies do extended students utilize to overcome struggles of not being able to graduate on time?